DETECTION OF TOXICANTS BASED ON LUMINESCENT REAGENTS - A. V. Sosnov; M. I. Vlasov; S. V. Sadovnikov; K. A. Rufanov; F. M. Semchenko; A. A. Sosnova; A. S. Radilov; E. I. Savelieva (Разработка и регистрация лекарственных средств, 2019)
Application of luminescent reagents for detection of toxicants including warfare agents, pesticides and their degradation products and precursors has been systematically reviewed. Methods of organophosphorus toxicants and products of their destruction (OP) detection based on lanthanide luminescent complexes (primarily Eu3+) have the similar sensitivity as the most advanced instrumental chromatographic and biochemical assays with detection level in the range of several ppts that allows to determine supertoxicants at the safety requirements concentration levels and at appropriate analysis duration from a few seconds to 10 minutes. High selectivity of toxicants identification is achieved by means of imprinted materials, modified cyclodextrins and luminescent sensor arrays. This is the basis for development of new technologies for trace analysis of toxicants and their decomposition products, including possible technology of luminescent contrast agents’ application to increase sensitivity of spectroscopic methods and remote determination of toxicants on the ground. Further possibilities to develop next generation materials for protective gear, equipment and multifunctional contact surfaces providing visualization and identification of toxicants and simultaneous catalytic self-decontamination is discussed. Relationship between technologies for improving safety and security at the crossroads of analytical chemistry of warfare agents, criminalistics, chemical safety and pharmaceutics has been demonstrated.